Persepsi guru SD Negeri Baturan terhadap penggunaan artificial intelligence pada Platform Merdeka Mengajar - Hilmy Majid Sanjaya; Riyadi Riyadi (Jurnal Pendidikan Dasar, 2026)
This study aims to analyze elementary school teachers’ perceptions of the use of Artificial Intelligence (AI) features on the Merdeka Mengajar Platform (PMM). Using a qualitative approach and phenomenological method, the research identifies three key indicators of teacher perception: involvement in AI-based learning, comparisons with previous teaching methods, and assessment and evaluation of AI effectiveness in education. The findings reveal that teachers’ use of AI remains limited, primarily in lesson planning, and has not been fully integrated into the instructional process. Major obstacles include a lack of technical knowledge and inadequate access to supporting technological infrastructure. Therefore, efforts such as training, outreach, and improving facilities are necessary to maximize AI adoption in education. This study underscores the importance of government, school, and teacher support in optimizing AI implementation to foster innovation and enhance the quality of elementary education.